2020
DOI: 10.22342/jme.11.2.10744.209-222
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Mathematical Problem-Solving Ability Based on Teaching Models Intervention and Cognitive Style

Abstract: The study aimed to analyze the interaction effect teaching models and cognitive style field dependent (FD)-field independent (FI) to students' mathematical problem-solving ability (MPSA), as well as students' MPSA differences based on teaching models and cognitive styles. Participants in this study were 145 junior high school students, with details of 50 students learning through the Connect, Organize, Reflect, and Extend Realistic Mathematics Education (CORE RME) model, 49 students use the CORE model, and 46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 30 publications
(34 reference statements)
3
20
0
8
Order By: Relevance
“…Based on those previous reports, it is necessary to further investigate the prospective teachers regarding how their expectation to their student's thinking processes. Therefore, the purpose of this study is to describe the expectations of prospective mathematics teachers for students' mathematical thinking processes in solving mathematical problems based on Polya's Model, such as: understanding the problem, devising a plan, carrying out the plan, and looking back (Hulaikah et al, 2020;Saiful et al, 2020;Son et al, 2020;Tohir, 2017;Yusnia, 2018); Then the problem solving used is related to the mathematical thought process theory expressed by Mason et al (2010), consisting of specializing, generalizing, conjecturing, and convincing (Farib et al, 2019;Iswari et al, 2019;Lane & Harkness, 2012;Lesseig, 2016;Sumarna & Herman, 2017). The following is a summary of the book "How To Solve It" concerning the Polya Model (Polya, 1973) in Table 1, it is stated that there are several stages to solve the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Based on those previous reports, it is necessary to further investigate the prospective teachers regarding how their expectation to their student's thinking processes. Therefore, the purpose of this study is to describe the expectations of prospective mathematics teachers for students' mathematical thinking processes in solving mathematical problems based on Polya's Model, such as: understanding the problem, devising a plan, carrying out the plan, and looking back (Hulaikah et al, 2020;Saiful et al, 2020;Son et al, 2020;Tohir, 2017;Yusnia, 2018); Then the problem solving used is related to the mathematical thought process theory expressed by Mason et al (2010), consisting of specializing, generalizing, conjecturing, and convincing (Farib et al, 2019;Iswari et al, 2019;Lane & Harkness, 2012;Lesseig, 2016;Sumarna & Herman, 2017). The following is a summary of the book "How To Solve It" concerning the Polya Model (Polya, 1973) in Table 1, it is stated that there are several stages to solve the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Proses untuk memecahkan suatu masalah matematika membutuhkan penerapan strategi penyelesaian masalah, dan dapat mengarahkan pemecah masalah untuk mengeksplorasi banyak ide dengan mengembangkan dan menguji hipotesis (Son, Darhim, & Fatimah, 2020). Sehubungan dengan proses pemecahan masalah, Foshay & Kirkley (2003) menawarkan model pemecahan masalah yang umum, yang dikenal dengan Bransford's IDEAL model, yaitu: 1) identifikasi masalah (identify), 2) mendefinisikan masalah dengan memikirkan dan memilah informasi yang relevan (define), 3) mengeksplor solusi dengan melihat alternatif, brainstorming, serta memeriksa berbagai kemungkinan (explore), 4) menyelesaikannya berdasarkan strategi (act), dan 5) memeriksa kembali serta mengevaluasi proses aktivitas (look back).…”
Section: Pendahuluanunclassified
“…Hundreds of quantitative studies on the effects of RME have been presented in the literature, but the analysis results are inconsistent. The analysis results from [8]- [10] for example, found that using the RME approach was effective in students' mathematical abilities. Meanwhile, [11], [12] reported that students' ability in the RME class was not better than the ability of students in conventional classrooms because these conflicting findings have triggered a meta-analysis study to reconcile the findings and produce more objective results [13].…”
Section: Introductionmentioning
confidence: 99%